1984
DOI: 10.1111/j.1348-0421.1984.tb00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Rickettsia tsutsugamushi Antigenically Different from Kato, Karp, and Gilliam Strains from Patients

Abstract: Rickettsia tsutsugamushi strains from three recent patients of Tsutsugamushi disease in Niigata Prefecture were isolated primarily in mice and then in L cell cultures. By this procedure, low virulent strains to mice, as well as high virulent ones, could be isolated and cultivated serially in L cell cultures, suggesting the usefulness of L cells for isolation of this species of rickettsia. Each newly isolated strain was identified as a member of R. tsutsugamushi from the results of cross immunological tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 9 publications
3
79
0
Order By: Relevance
“…[22][23][24][25] In Korea, the Boryong serotype was reported to be distributed throughout the country except for Cheju Island. 26 The Karp and Gilliam serotypes were prevalent in Taiwan, whereas the Gilliam serotype was prevalent in China.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] In Korea, the Boryong serotype was reported to be distributed throughout the country except for Cheju Island. 26 The Karp and Gilliam serotypes were prevalent in Taiwan, whereas the Gilliam serotype was prevalent in China.…”
Section: Discussionmentioning
confidence: 99%
“…The prototype strains of Gilliam, Karp, and Kato were plaque-purified in our laboratory. Shimokoshi strain was isolated from a patient and demonstrated to be antigenically distinguishable from prototype strains (9). All rickettsial strains used in this study were propagated in the monolayer or suspension cultures of L-929 cells as described previously (8).…”
Section: Methodsmentioning
confidence: 99%
“…The prototype strains of Gilliam, Karp, and Kato are generally recognized, and other antigenic types such as Shimokoshi and Kawasaki strains have been isolated (9,12). Our recent comparative immunoblotting analyses of these variants with guinea pig hyperimmune sera and strain-specific monoclonal antibodies demonstrated that the major polypeptide of 54 to 56 kilodalton (54-56K) on the rickettsial surface is antigenically strain-or type-specific, whereas the 70K and 46-47K polypeptides are group-specific (5,10).…”
mentioning
confidence: 99%
“…90 %) of the sera ( Table 6). The antibodies in the remaining 10% may be against common group antigen among Kato, Karp, and Gilliam strains, or against antigen of Rt other than the 3 strains, or against some unknown infectious agent, but the former two possibilities are more likely, because new strains of Rt possessing type-specific antigen (s) different from those of the 3 strains have been isolated (23,24). Any infectious agent sharing antigens common with Rt has not been reported except Proteus vulgaris, and Rtspecific seroconversion has been observed at a remarkable frequency in the endemic area (Table 4).…”
Section: Discussionmentioning
confidence: 99%